The Language of Social Research. - Lazarsfeld, Paul F. and Moris Rosenberg (New York THE FREE PRESS, 1967)
This volume, which carries the subtitle of A reader in methodology of social research will puzzle readers who attempt to justify its existence by the title.
Keywords: Science